2017
DOI: 10.1111/bcp.13192
|View full text |Cite
|
Sign up to set email alerts
|

Is there potential for therapeutic drug monitoring of biologic agents in rheumatoid arthritis?

Abstract: The use of biologics has significantly changed the management of rheumatoid arthritis over the last decade, becoming the cornerstone treatment for many patients. The current therapeutic arsenal consists of just under 10 biologic agents, with four different mechanisms of action. Several studies have demonstrated a large interindividual pharmacokinetic variability, which translates to unpredictability in clinical response among individuals. The present review focuses on the pharmacokinetics and pharmacodynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In accordance with previous studies, we showed that serum tocilizumab concentrations around 0.9 μg/mL are sufficient to normalize baseline CRP and ESR values. This normalization occurs rapidly from the initiation of treatment, with an estimated half‐life of approximately 2 weeks, as seen in the principal tocilizumab clinical trials . On the other hand, TJC, SJC, PGA and EGA formed the second group of variables.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In accordance with previous studies, we showed that serum tocilizumab concentrations around 0.9 μg/mL are sufficient to normalize baseline CRP and ESR values. This normalization occurs rapidly from the initiation of treatment, with an estimated half‐life of approximately 2 weeks, as seen in the principal tocilizumab clinical trials . On the other hand, TJC, SJC, PGA and EGA formed the second group of variables.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, there is still debate on which continuous composite measure should be chosen to evaluate disease activity in RA patients under tocilizumab treatment as there is concern about the impact of the steep reduction in CRP and ESR values within the first 4 weeks of tocilizumab treatment on disease activity . Nishimoto et al investigated the correlation between DAS28 and other disease activity measures in RA patients treated with tocilizumab.…”
Section: Discussionmentioning
confidence: 99%
“…A definitive treatment for all RA patients has not been discovered [ 23 , 161 – 164 ]. A multitarget approach is required to better control the disease, and several pathways must be considered to completely treat RA.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…To date, several reviews have summarized the studies assessing the exposure-response relationships and optimal concentration thresholds for mAbs in inflammatory diseases [ 22 , 23 , 24 , 25 , 26 ]. It seems the consensus and guidelines for TDM and target mAb concentrations are best established in the field of Gastroenterology, but the advances are continuously made in the management of rheumatic and dermatologic conditions, as well ( Table 1 ) [ 23 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Therapeutic Drug Monitoring Of Monoclonal Antibodiesmentioning
confidence: 99%